2013
DOI: 10.1063/1.4848936
|View full text |Cite
|
Sign up to set email alerts
|

Note: An ion source for alkali metal implantation beneath graphene and hexagonal boron nitride monolayers on transition metals

Abstract: The construction of an alkali-metal ion source is presented. It allows the acceleration of rubidium ions to an energy that enables the penetration through monolayers of graphene and hexagonal boron nitride. Rb atoms are sublimated from an alkali-metal dispenser. The ionization is obtained by surface ionization and desorption from a hot high work function surface. The ion current is easily controlled by the temperature of ionizer. Scanning Tunneling Microscopy measurements confirm ion implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In previous work we reported the formation of Ar and Rb nanotents by the exposure of the h -BN nanomesh to low energy ions. , The immobilization of atoms occurs at two distinct sites beneath the “wire crossings” of the h -BN nanomesh superhoneycomb. It was found that the implantation length ( i .…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In previous work we reported the formation of Ar and Rb nanotents by the exposure of the h -BN nanomesh to low energy ions. , The immobilization of atoms occurs at two distinct sites beneath the “wire crossings” of the h -BN nanomesh superhoneycomb. It was found that the implantation length ( i .…”
mentioning
confidence: 98%
“…20,27 In previous work we reported the formation of Ar and Rb nanotents by the exposure of the h-BN nanomesh to low energy ions. 24,28 The immobilization of atoms occurs at two distinct sites beneath the "wire crossings" of the h-BN nanomesh super-honeycomb. It was found that the implantation length (i.e., the distance that Ar atoms move after penetration beneath the h-BN monolayer before they localize in nanotents) is about 8 nm and the occupation ratio between the two distinct sites is influenced by the ion dose and the annealing temperature.…”
mentioning
confidence: 99%
“…Recently, intercalation processes of Ar and Rb, forming the so-called 'nanotent' structures, have been reported after exposure of the h-BN nanomesh to low energy ions. [38,39] The ion bombardment sputters out boron and nitrogen atoms, leaving vacancy defects within the h-BN layer, which are visible at the rim and at the wire of the nanomesh by STM. Interestingly, an annealing of the defective system leads to self-healing processes, where the defects seem to gather, first forming larger defects and then inducing reconstruction of the monolayer (formation of holes and self-healing).…”
Section: Formation Of B and N Vacanciesmentioning
confidence: 99%
“…In previous work, we reported the formation of Ar and Rb nanotents by 50 exposing low energy ions to the h-BN/Rh(111) nanomesh [1,40]. The immobilization of atoms occurs at two distinct sites beneath the "wire crossings" of the h-BN nanomesh honeycomb [41].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The supercell is divided into three different regions with different registries of 40 the carbon atoms to the Ru atoms in the first substrate layer [24]. Two of these regions, where one of the two carbon atoms of the 1 × 1 honeycomb unit cell of graphene bind to a Ru atom are called "valley" and the third region is named as "hill", where the carbon does not bind to the substrate, but is stabilized by the strong sp 2 σ-bonds.…”
Section: Accepted Manuscriptmentioning
confidence: 99%